The Effect of Murothal Al-Qur’an Therapy on Reducing Anxiety and Quality of Life on Pregnant Women - Indrawati Indrawati; Yufdel Yufdel; Eqlima Elfira (JURNAL KEBIDANAN, 2022)
Pregnancy is a critical psychological social transition period that requires family, social and health support. Pregnancy causes psychological changes that will have an impact on the baby. These changes will affects the quality of life of pregnant women. This study was to determine the effect of murothal Al-Qur’an therapy in reducing anxiety in improving the quality of life of pregnant women in Medan Sunggal District. The type of research is pre-experimental using one intervention group. This research was conducted in Medan Sunggal District with sample of 30 respondents with several research criteria. The measuring instrument used the Hamilton Rating Scale for Anxiety (HRS-A) and the WHOQOL-BREF Questionnaire for quality of life which was administered after the intervention. Wilcoxon test was carried out to determine the effect of Murothal Al-Qur’an (Surah Al-Fatihah) therapy in reducing anxiety and in improving the quality of life of pregnant women. The result showed that there was an effect of Murothal Al-Qur’an (Surah Al-Fatihah) therapy on reducing anxiety and quality of life of pregnant women. The significant value obtained was 0.000 (p 0.05), which means that there was a significant difference between after the intervention in reducing anxiety and the quality of life of pregnant women. Murothal Al-Qur’an (Surah Al-Fatihah) is very beneficial for pregnant women in reducing anxiety and improving the quality of life in dealing with pregnancy. Murothal al-qur'an is recommended for anyone, not only for pregnant women, especially those who are Muslim to cope with  anxiety.